2020
DOI: 10.21203/rs.2.24617/v1
|View full text |Cite|
Preprint
|
Sign up to set email alerts
|

WITHDRAWN: Silent information regulator 1 ameliorates oxidative stress injury via PGC-1α/PPARγ-Nrf2 pathway after ischemic stroke in rat.

Abstract: Background Astrocytes mediate brain defense against oxidative stress-induced injury. Silent information regulator 1 (SIRT1) has anti-oxidative stress effects in many diseases and is highly expressed in astrocytes. However, the neuroprotective effects of SIRT1 on astrocytes after cerebral ischemia/reperfusion injury are unclear. Methods Here, we evaluated the effects of SIRT1 in astrocytes after cerebral ischemia/reperfusion injury using oxygen-glucose deprivation/recovery in astrocytes in vitro and middle cere… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 45 publications
0
0
0
Order By: Relevance
“…The other paper of significance in the current issue of the World Journal of Gastroenterology , acknowledged by us, is the original paper by Zhou et al [ 15 ].…”
Section: Novel Insights Into Mechanisms Of Acute Liver Failurementioning
confidence: 99%
See 1 more Smart Citation
“…The other paper of significance in the current issue of the World Journal of Gastroenterology , acknowledged by us, is the original paper by Zhou et al [ 15 ].…”
Section: Novel Insights Into Mechanisms Of Acute Liver Failurementioning
confidence: 99%
“…The study by Zhou et al [ 15 ] used mainly mouse and cell models but not clinical settings. Although their research demonstrated reduced expression of SIRT1 in human ALF liver tissue, the effectiveness of SIRT1 activators in treating acute liver injury and failure remains uncertain.…”
Section: Novel Insights Into Mechanisms Of Acute Liver Failurementioning
confidence: 99%